TYPES OF NUTRIENT MEDIA FOR CULTIVATING MICROALGAE AND THEIR PREPARATION PROCEDURES (Scientific journal of the Fergana State University, 2025)
Today, the global population is growing at a rapid pace. This trend is leading to an increased demand for food resources, particularly for aquaculture products. In this situation, ensuring food security and effectively utilizing biological resources has become one of the key issues. The aquaculture sector, especially the enrichment of the feed base for aquatic organisms such as fish, crustaceans, and aquatic plants, is crucial and requires the development of sustainable production technologies.Young biotechnology scientists face a number of priority tasks, including:• Developing optimal nutrient media for large-scale cultivation of microalgae and enriching their composition.• Creating high-protein and environmentally safe feed products to improve aquaculture feed quality.• Automating biotechnological processes and enhancing economic efficiency.• Designing and implementing innovative bioreactor systems to improve production processes.Furthermore, there is a need for technologies that minimize environmental harm in the production of aquaculture products. The scientific research and use of modern technologies by young scientists not only facilitate the production processes but also contribute to ensuring ecological sustainability. Therefore, the research being conducted in this field plays a significant role in addressing today's global challenges.